The cooling effect from afforestation as a solution to urban heating: a case study in Teresina, Piauí state, Brazil (Research, Society and Development, 2020)
Green areas in urban centers can contribute to the thermal control of “urban heat islands.” Within the context of climate change, with rising temperatures, drier climates, and increasingly frequent heat waves, green areas are becoming progressively important, as they can create a cooling effect that might extend into its surrounding areas. This study analyzes within the “health pole” of the city of Teresina, an area with a high urban density, how the afforestation of the region affects the thermal aspect of the selected region. Climatic parameters were measured (ambient temperature, thermal sensation, the relative humidity of the air, wind speed) at selected points within a defined area, starting at the ends of the center of this area, all points had different orientations and exposure to the sun. It was found that in areas where afforestation existed, temperatures were lower in both shade and areas exposed to the sun. Despite local climatic conditions, in particular the low wind speed, solar exposure, and urban geometry are the main factors that influence the found temperatures. The cooling effect caused by urban afforestation can be better understood with additional measurements at different times of the year in the same region.